Preventing Central Venous Catheter Misplacement: Lessons from a Catheter Malposition (Bangladesh Critical Care Journal, 2026)
Central venous catheter (CVC) insertion is not only a very crucial procedure in critical care areas but also a very risky one. Performing the procedure under ultrasound guidance has improved safety, however, catheter malposition remains a frequent complication. Malposition bears risks of dysfunction and thrombosis. In this case report, we look into the case of a 26 years old female with recurrent pancreatitis who developed septic shock and required CVC placement. Chest X-ray done after the procedure revealed misplacement of the catheter tip in the ipsilateral subclavian vein rather than the lower third of the superior vena cava (SVC). The catheter was then removed immediately and replaced under ultrasonography (USG) guidance. We are going to delve into the anatomical and technical factors causing such malposition as well as the role of methods like manometry and electrocardiographic (ECG) tip navigation to complement USG for real-time tip confirmation. We close our discussion with saying that a multi-modal approach, pushing beyond the limits of USG-guided catheter placement, is essential to prevent such predicament and its associated morbidity, particularly in unstable patients where landmark techniques may be attempted.Bangladesh Crit Care J March 2026; 14 (1): 68-70